Searching for ethics. Legal requirements and empirical issues for anthropology - Perrin, Julie; Bühler Viredaz, Nolwenn; Berthod, Marc-Antoine; Forney, Jérémie; Ossipow-Wuest, Laurence; Kradolfer, Sabine (My University, 2018)
This paper analyses the new legal provisions impacting qualitative research practices and contributing to the institutionalization of research ethics in Switzerland. After contextualizing the emergence of new forms of research regulation, it shows how their epistemological assumptions challenge anthropology. It then explores the issues related to the articulation between procedural ethics and processual ethics. Finally, it discusses the different postures which might possibly be adopted by scholars in anthropology and other qualitative social sciences
Keywords: éthique de la recherche; Suisse; ethnologie; anthropologie